Quinquelaophonte Aurantius sp. nov., a new harpacticoid species (Copepoda: Harpacticoida: Laophontidae: Quinquelaophonte) from New Zealand. Issue 4 (2nd October 2019) - Charry, Maria P.; Wells, John B. J.; Keesing, Vaughan; Smith, Kirsty F.; Stringer, Tristan J; Tremblay, Louis A.
ABSTRACT: The new species Quinquelaophonte aurantius sp.nov. is described, based on specimens collected in Portobello Bay, New Zealand. The species is distinguishable for having long fine setules in the anal operculum distal edge, a breadth ratio of caudal rami length above 3.5, and a rudimentary antenna abexopodal spine. This new species differentiates from Q. parasigmoides and Q. wellsi on the following autapomorphs; short spine-like outer seta in segment 2 of females P3 endopod and the partial reduction of setae in spines from male P3 and P4, longer V-shaped caudal rami, an almost non-existent terminal portion of the antenna exopod with short lateral setae. Phylogenetic analyses demonstrate the position of Quinquelaophonte within the family Laophontidae. Publication LSID: urn:lsid:zoobank.org:pub:D5E5EB23-8348-446D-9606-EA8B27EC0EDC LSID for Q. aurantius: urn:lsid:zoobank.org:act:834C4218-209B-4B70-8AD5-35512B5FCB29